A new peptide ligand for colon cancer targeted delivery of micelles. (12th June 2016) - Ren, Yachao; Mu, Yu; Song, Yanping; Xie, Jinxin; Yu, Hui; Gao, Sainan; Li, Sen; Peng, Haisheng; Zhou, Yulong; Lu, Weiyue
Abstract: Ligands are an imperative part of targeted drug delivery systems, and choosing a ligand with high affinity is a subject of considerable interest. In this study, we first synthesized a 12-residue peptide (TK) that interacts with integrin α6 β1 overexpressed on colonic cancer cells. The molecular binding affinity assay indicated that TK had a high binding affinity for integrin α6 β1 . The results of cellular and tumor spheroid uptake suggested that TK peptide not only increases Caco-2 cells uptake, but also effectively increases penetration of the tumor spheroids. TK-conjugated PEG-PLA was synthesized to prepare a novel PEG-PLA micelles loading DOX or coumarin-6 (TK-MS/DOX or TK-MS/C6). The obtained TK-MS/DOX exhibited uniform, spherical shape with a size of 23.80 ± 0.32 nm and zeta potential of 12.21 ± 0.31 mV. The release behavior of DOX from micelles were observed no significant changes after TK modification, however, the release profile exhibited pH-sensitive properties. Compared with MS/DOX, TK-MS/DOX exhibited significantly stronger cytotoxicity for Caco-2. Confocal laser microscopy and flow cytometry data further indicated that the targeting micelles not only had higher uptake by Caco-2 cells, but also more effectively penetrated the tumor spheroids. Therefore, TK peptide appears to be suitable as a targeting ligand with potential applications in colonic targeted therapy.